Thoracic radiotherapy plus Durvalumab in elderly and/or frail NSCLC stage III patients unfit for chemotherapy - employing optimized (hypofractionated) radiotherapy to foster durvalumab efficacy: study protocol of the TRADE-hypo trial - Bozorgmehr, Farastuk; Chung, Inn; Christopoulos, Petros; Krisam, Johannes; Schneider, Marc; Brückner, Lena Marie; Müller, Daniel Wilhelm; Thomas, Michael; Rieken, Stefan (BMC cancer, 2020)
Non-small cell lung cancer is the most common cause of cancer death worldwide, highlighting the need for novel therapeutic concepts. In particular, there is still a lack of treatment strategies for the group of elderly and frail patients, who are frequently not capable of receiving standard therapy regimens. Despite comprising the majority of lung cancer patients, this group is underrepresented in clinical trials. This applies also to elderly and frail patients suffering from unresectable stage III NSCLC, who are unfit for chemotherapy, and, therefore, cannot receive the standard therapy comprising of radiochemotherapy and the recently approved subsequent durvalumab consolidation therapy. These patients often receive radiotherapy only, which raises the concern of undertreatment. The TRADE-hypo trial aims at optimizing treatment of this patient group by combining radiotherapy with concomitant durvalumab administration, thereby employing the immune-promoting effects of radiotherapy, and determining safety, feasibility, and efficacy of this treatment.